2018
DOI: 10.1002/chem.201804027
|View full text |Cite
|
Sign up to set email alerts
|

Trifluoromethanesulfinyl Chloride for Electrophilic Trifluoromethythiolation and Bifunctional Chlorotrifluoromethythiolation

Abstract: Trifluoromethanesulfinyl chloride (CF3SOCl) has been introduced as a new reagent for C−H trifluoromethylthiolation of indoles, thiophenes, and ketones under catalyst‐free conditions and in the absence of reductant. The disproportionation of CF3SOCl to CF3SO2Cl and CF3SCl provides two pathways for the trifluoromethylthiolation. Direct trifluoromethylthiolation with CF3SCl or trifluoromethylsulfoxidation with CF3SOCl is followed by reduction with CF3SOCl. This reagent can be used to functionalize benzothiophenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
23
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 69 publications
0
23
0
1
Order By: Relevance
“…reported the trifluoromethylthiolation of ketones with CF 3 SOCl [Scheme , Eq. (2)] . In our continuous study on the development of trifluoromethylthiolation methods with easily available and cheap reagents, it was found that the trifluoromethylthiolation‐based bifunctionalization of β‐diketones could be achieved with CF 3 SOCl [Scheme , Eq.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…reported the trifluoromethylthiolation of ketones with CF 3 SOCl [Scheme , Eq. (2)] . In our continuous study on the development of trifluoromethylthiolation methods with easily available and cheap reagents, it was found that the trifluoromethylthiolation‐based bifunctionalization of β‐diketones could be achieved with CF 3 SOCl [Scheme , Eq.…”
Section: Methodsmentioning
confidence: 99%
“…Based on the experimental results and literature reports, a plausible mechanism was proposed for the above reactions as showed in Scheme . The reaction of 1 and base affords anion intermediate A , which reacts with CF 3 SOCl to give compound B .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…以 CuBr 为催化剂, 用含有手性萘胺的烯胺化合物与该 试剂在甲苯中室温反应, 可以中等的收率得到含有 SCF 2 H 的手性化合物, ee 值最高可达 93% (Scheme 4) [36] . [41] 在研究三氟甲基亚磺酰氯 [55] . 2016 年, Glorius 课题组 [56]…”
unclassified